COVID-19 Outcomes in Patients Undergoing B Cell Depletion Therapy and Those with Humoral Immunodeficiency States: A Scoping Review - Jessica Jones; Aiman Faruqi; James Sullivan; Cassandra Calabrese; Leonard Calabrese (Case Western Reserve University, 2021)
Background: The role of humoral immunity has been well established in reducing infection risk and facilitating viral clearance in patients with COVID-19. However, the relationship between specific antibody responses and severity of COVID-19 is less well understood.  Methods: To address this question and identify gaps in knowledge, we utilized the methodology of a scoping review to interrogate risk of infection and clinical outcomes of COVID-19 in patients with iatrogenic and inborn humoral immunodeficiency states based on existing literature.  Results: Among patients with iatrogenic B-cell depletion, particularly with agents targeting CD20, our analysis found increased risk of severe COVID-19 and death across a range of underlying disease states. Among patients with humoral inborn errors of immunity with COVID-19, our synthesis found that patients with dysregulated humoral immunity, predominantly common variable immunodeficiency (CVID), may be more susceptible to severe COVID-19 than patients with humoral immunodeficiency states due to X-linked agammaglobulinemia and other miscellaneous forms of humoral immunodeficiency. There were insufficient data to appraise the risk of COVID-19 infection in both populations of patients.  Conclusions: Our work identifies potentially significant predictors of COVID-19 severity in patients with humoral immunodeficiency states and highlights the need for larger studies to control for clinical and biologic confounders of disease severity.